Level of IL-6 and IL-8 and their associations with non-alcoholic fatty liver disease in patients with type 2 diabetes - Mykhalchyshyn , Galyna; Kobyliak , Nazarii; Komisarenko , Iuliia (The Ukrainian Scientific Medical Youth Journal, 2023)
non-alcoholic fatty liver disease (NAFLD) is indicated by the accumulation of lipids within the hepatocytes exceeding 5% of liver weight without excessive alcohol intake and secondary liver diseases. The efforts of many scientists worldwide are focused on improving the understanding of pathogenic processes and triggers of NAFLD progression, with an emphasis on the simultaneous study of several pathophysiological pathways to identify disorders throughout the disease spectrum. The aim was to examine the serum levels of IL-6 and IL-8 and its associative relationships with anthropometric parameters and metabolic profiles in patients with T2D, depending on the presence of NAFLD. This cross-sectional study involved 375 patients aged 40–80 with type 2 diabetes. They were divided into 3 groups. The control group included 98 T2D patients without NAFLD. The main group included T2D patients with NAFLD, which was separated into two subgroups depending on the level of transaminases: normal (group 2A, n=150) and increased (group 2B, n=127) transaminases group. In order to identify predictors of rapid progression of liver fibrosis in patients with T2D, a sub-analysis was conducted, which included 82 patients from group 2. We found significant relationships between the level of studied interleukins and the components of the metabolic syndrome. Both IL-6 and Il-8 levels are significantly associated with gender, duration and severity of T2D, BMI, ALT, AST and total bilirubin level in a simple logistic regression analysis. However, step-by-step multiple logistic regression analysis revealed no reliable link between both cytokines and NAFLD development. From the other hand elevated IL-8 and decreased IL-6 had a significant effect on the fibrosis progression in patients with NAFLD associated with T2D. Our study has demonstrated significant links between the level of IL-6 and IL-8 and the components of the metabolic syndrome such as obesity or transaminase activity, but not with NAFLD itself.